Technics Of Soul Purifying As Religious Experiences And Practices Of Cianjur Thariqat Al-Tijaniyah (CTAT) Teaching Followers - Dadang Ahmad Fajar (Khazanah Sosial, 2022)
The purification of the soul is one of the spiritual activities of humans in the process of cleansing their souls so that life can be calm, understand the nature of truth and become good people through religious practice. Many humans feel uneasy, along with the times that continue to experience changes and trends in consumptive lifestyles. However, in the midst of a society that is undergoing changes due to situations of social change and lifestyle trends, there is a group of Muslims who are members of the Tariqat Al-Tijaniyah Cianjur community trying to live in peace. They try, understand the nature of truth and try to be good people through purification of the soul as a religious experience. The aim of this paper is to understand the technical way of cleansing the soul as a religious experience according to the followers of Thariqat Al-Tijaniyah Cianjur. The method used in this study is a qualitative method by describing the religious experience of the followers of Tariqat Al-Tijaniyah in Cianjur through words. The theory used is the theory of soul purification according to Shaykh Ahmad Al-Tijani. The findings show that the followers of Tariqat Al-Tijaniyah in Cianjur practice the syar'i tradition, often read magical texts so they feel confident in their souls and often recite certain prayers. The conclusion shows that the followers of Tariqat Al-Tijaniyah Cianjur understand that they are committing soul praise as a religious experience.